BACTERIA FROM ARBUSCULAR MYCORRHIZAL FUNGI SPORES Gigaspora sp. AND Glomus sp.: THEIR ANTAGONISTIC EFFECTS TOWARDS SOILBORNE FUNGAL PATHOGENS AND GROWTH STIMULATION OF Gigaspora sp. in vitro - Sri Wilarso Budi (SEAMEO BIOTROP, 2013)
Eight isolates bacteria were isolated from surface sterilized endomycorrhizal spores of Gigaspora sp and six isolates bacteria isolated from Glomus sp. The tests to the antagonists against fungal pathogens and stimulation of endomycorrhizae hyphal development of Gigaspora sp in vitro showed that there were three.isolates (GG1, GG5 and GL3) that have the ability to inhibit the growth of pathogens and enhance the development of hyphae in vitro. Enzymatic activity test showed that there were seven isolates that produce cellulase and protease activity that is GG1, GG3, GG6, GG7, GL2, GL4 and GL6